2021
DOI: 10.5430/ijfr.v12n4p156
|View full text |Cite
|
Sign up to set email alerts
|

Treasury Single Account Policy and Revenue Generation Among Federal Parastatals in Ekiti-State, Nigeria

Abstract: Treasury Single Account (TSA) is a new government policy to fight corruption in the Nigerian public sector. The policy has received a lot of compliments from many Nigerians; however, empirical studies have produced mixed results. The study examined the effects of Treasury Single Accounts (TSA) on the revenue generation of federal government parastatals in Ekiti state. The study specifically examined the effect of TSA on revenue generation of Federal University Oye-Ekiti, Federal Teaching Hospital Ido, Federal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Also posited out by the result was that TSA reduces the level of idle cash with commercial banks. More recently, Ogungbade et al [15] using paired sample t-test examine the effect of TSA on revenue generation of some federal MDAs in Ekiti State and the result therefrom revealed that, TSA has not enhanced the revenue generation among federal MDAs in Ekiti State and that TSA is counterproductive in the State. This study is underpinned by the Institutional-centric theory of finances and resources-based theories.…”
Section: Literature Review and Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also posited out by the result was that TSA reduces the level of idle cash with commercial banks. More recently, Ogungbade et al [15] using paired sample t-test examine the effect of TSA on revenue generation of some federal MDAs in Ekiti State and the result therefrom revealed that, TSA has not enhanced the revenue generation among federal MDAs in Ekiti State and that TSA is counterproductive in the State. This study is underpinned by the Institutional-centric theory of finances and resources-based theories.…”
Section: Literature Review and Empirical Studiesmentioning
confidence: 99%
“…This sparked the interest of scholars, researchers, financial analysts, and policymakers to identify the effect of TSA on PFM in Nigeria. Several studies were conducted in Nigeria to find the effect of TSA implementation on PFM [1,3,4,9,15]. The findings from these studies are still contradictory and most of the studies conducted are carried out in the Southern part of the country, hence the need to ascertain whether the introduction of TSA in Nigeria aided in the elimination of fraud in Nigeria with particular reference to federal MDAs in Sokoto State.…”
Section: Introductionmentioning
confidence: 99%